Effectiveness of a Training Module in Detecting Developmental Delays in Children (0-6 Years) by Frontline Workers in a Rural Setting of Odisha: A Cluster Randomized Trial - Dora, Susmita; Bhatia, Vikas; Behera, Binod Kumar; Satapathy, Amit Kumar (Research Highlights in Disease and Health Research Vol. 6, 2023)
The objective of this chapter is to build the capacity of frontline workers (FLWs) and assessment of effectiveness of a modular training strategy in detection of developmental delays in children less than 6 years of age using a cluster randomized trial approach. In India, screening and management of childhood diseases are hampered by a lack of doctors and paediatricians at the community level (village and block). Rashtriya Bal Swasthya Karyakram (RBSK) was established under the NRHM in 2013 to provide free screening for birth defects, diseases, deficiencies, and disabilities to children aged 0 to 18. A community based interventional study was conducted in Tangi block having a total population of 1,67,144 and 0-6 years population of 19,445 as per census 2011, in Khurdha district of Odisha. The training module was created by referring to the training module for medical officers in the RBSK mobile health team, which was then translated into regional language (Oriya). One of the authors (AKS) validated the final translated module. The anganwadi workers (AWWs) and the accredited social health activists (ASHAs) in one study arm were trained using a structured training module specifically developed in regional language for screening children for developmental delay (DD). A total of 35 AWWs and 25 ASHAs in intervention arm and 27 AWWs and 26 ASHAs in control arm were recruited in the study. The FLWs in the intervention arm could detect 8 children with DD after training and FLWs in control arm could detect 1 child with DD. With a sample of 870 children in the intervention arm and 847 children in the control arm, the investigator discovered that the prevalence of DD was 1.3% in the intervention arm and 1.4% in the control arm. Training of the FLWs using a training module in regional language helped in identification of children in 0-6 years age group having developmental delays (DDs). Hence, the government should take into account AWW and ASHA capacity building so that they can be integrated into the health system and the RBSK program for screening children.